Pengembangan Produk Beras Jagung Instan : Kajian Penerimaan Sensoris, Karakteristik Kimia, dan Analisis Biaya Produksi - Ekafitri, Riyanti (Perum BULOG, 2016)
Development of instant rice-corn is intended to provide an alternative of staple foods besides rice. Fortification of fiber (fiber addition) is done to replace the fiber loss during grinding and milling process aswell to improve the nutritional quality of instant rice-corn. In this study, the treatment is the addition of different fiber types on instant rice-corn, which is: without fiber (A), fiber agar-agar powder addition (B) and fiber agar-agar powder & carrot porridge (C). This study aimed to examine the sensory evaluation, chemicalcharacteristics, and costs of production of instant rice-corn. Based on the sensory evaluation, the productis accepted by the panelists with an assessment of rather preferred. Instant rice-corn with fiber agar-agarpowder & carrot porridge is the best treatment with chemical characteristics: water content 7,38 percent,ash content 1,04 percent, protein 5,06 percent, carbohydrate 69,90 percent, and crude fiber 3,48 percent.Costs production of 10 kilograms of instant rice-corn is Rp 116.348,00, the selling price is Rp 157.070,00per kilogram with a profit margin of 35 percent.